Geometric thinking and reasoning abilities of fourth year high school students - Liwag, Jacinto M. (2008)
This study examined the geometric thinking and reasoning abilities of 319 students from a private high school and 207 students from a science high school, both in Quezon City. It used the researcher-made Geometric Thinking and Reasoning Ability Test, which was validated by a panel of experts, was pilot-tested, and was found to be reliable. The students' reasoning abilities were analyzed based on the Theory of Figural Concept involving the conceptual and figural components. The overall performance of students from both schools was at 50 percent suggesting low thinking and reasoning abilities in Geometry. The students from the science high school performed consistently better than those from the private school in the test and in all topics of Plane Geometry and in terms of visual, descriptive/analytic, and abstract/relational thinking. Misconceptions were predominant, indicating inadequate knowledge in Geometry and insufficient analytical thinking skills.